ANALISIS PENYERAPAN TENAGA KERJA DI KABUPATEN TIMUR TENGAH SELATAN PROPINSI NUSA TENGGARA TIMUR - Louise Eunike Tomasowa (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2014)
The research is analyzing the absorption of workers at TTS East Nusa Tenggara Province . Research aims at: identifying sectors with the strength of absorbing workers; understanding the output produced by sector workers at TTS; and acknowledging how is the effect of the economic growth on the absorption of workers at TTS. Analysis tools are Location Quotient (LQ), TK Productivity, TK Elasticity, MRP, and Klassen Typology. Result of research indicates that mining and quarring sector, and electricity, gas and water sectors are superior sectors in absorbing workers.Keywords : TK Absorption , Location Quotient, TK Productivity, TK Elasticity, MRP